Public speaking anxiety and self-efficacy among Sudanese medical students: a cross-sectional study - Weam Mohamed Meargni Ahmed; Malaz M. Abdalmotalib; Galia Tajelsir Fadulelmula Mohammed; Musab Mohammed Yassin Siddig; Hajar Saad Salih; Alemam Awad Alameen Ahmed; Sharifa salahEldeen Abdullateef (BMC Psychology)
Abstract Background Public speaking is a critical skill for medical professionals, yet many students experience public speaking anxiety (PSA), which negatively impacts mental well-being, academic performance, and professional growth. PSA is closely linked to self-efficacy, which serves as a protective factor against stress and anxiety. Understanding this relationship is vital, particularly in Sudan, where cultural and systemic factors may influence both PSA and self-efficacy. Methods This cross-sectional based analytical study was conducted among 1130 Sudanese medical students from multiple universities, this design was well-selected considering the current circumstances of Sudan conflict. Data were collected using validated tools: the Personal Report of Public Speaking Anxiety (PRPSA) scale and the General Self-Efficacy (GSE) scale. Convenience sampling was employed, and data analysis including descriptive statistics, correlation analysis, and regression models was conducted to identify factors influencing PSA. Results Nearly half of the participants (45%) experienced moderate PSA, while 11.5% exhibited high PSA. Conversely, 87% reported high self-efficacy. PSA was significantly associated with gender, academic performance, extracurricular activities, and family income. A weak negative correlation was observed between PSA and self-efficacy (Spearman’s rho = -0.189, p < 0.001), indicating that higher self-efficacy mitigates PSA. Conclusions PSA is highly prevalent among Sudanese medical students, with cultural and academic factors playing a crucial role. The study highlights the need for targeted interventions to build self-efficacy and reduce PSA, such as structured training, extracurricular opportunities, and culturally tailored approaches to public speaking in medical education. Trial registration Not applicable.